Well-being concepts and components - TOV, William (Institutional Knowledge at Singapore Management University, 2018)
Well-being is a broad, multifaceted construct. This chapter reviews different ways of defining and measuring well-being and the implications this has for understanding the correlates and causes of well-being. Hedonic well-being (HWB), eudaimonic well-being (EWB), and other conceptions of well-being are discussed. Specific components and aspects of HWB are elaborated on. These include the distinction between affective and cognitive well-being. Major aspects of affective well-being include valence, frequency versus intensity, arousal, and interpersonal engagement. Major aspects of cognitive well-being include life satisfaction, life evaluation, and domain satisfaction. Processes underlying the structure of cognitive well-being are discussed including top-down versus bottom-up models, and the tendency to use heuristics versus stable sources of information to evaluate one’s life. Trait versus state conceptions of well-being are introduced. Different well-being assessment methods (online, recall, global) can be located on a state-trait continuum. The distinction between state and trait measures of well-being has implications for understanding the structure of affect, the relation between well-being and health, and cultural variation in well-being. Future research is needed to clarify the distinct correlates of affective versus cognitive well-being, as well as how positive and negative emotions are operationalized. In addition, a better understanding of the components of EWB and how they are related to HWB and affective dimensions beyond valence will shed light on the validity of the EWB construct. Finally, greater sensitivity to the state-trait distinction will deepen our knowledge of the processes that shape both HWB and EWB.